Sky view factor and thermal comfort analysis using hemispheric images from Google Street View and wavelet in an urban ecosystem of the Brazilian Cerrado - Rocha, Angela Fatima da; Silva, Ernany Paranaguá da; Musis, Carlo Ralph de; Nogueira, Marta Cristina de Albuquerque (Ciência e Natura, 2018)
This article aims to analyse the sky view factor (SVF) in one of the hottest cities of the Brazilian Cerrado, and its correlation with thermal comfort in two urban sections with different characteristics, as well as the physiological equivalent temperature (PET) and predicted mean vote (PMV) indices, complemented by a characterisation in the frequency field for a 12-month cut-off in the same year of relative air temperature and humidity. The study area was located in the central region of Cuiabá, Mato Grosso, due to the presence of regions with high urbanisation indices and small parks; one section composed of afforested area and second section composed of varied buildings. To obtain the SVF, the Google Street View image database was used, from which fisheye images were reconstructed and the SVF was determined using RayMan software. The PET and PMV indices were determined for the morning, afternoon, and evening, with comfort in the morning and discomfort in the afternoon and evening. Traditional Morlet wavelets were plotted for time series of relative air temperature and humidity for the year 2015, which qualitatively demonstrated some of the dynamics of these micrometeorological variables for tropical Cerrado climate.